Aborsi Dalam Perspektif Al-Qur’an (Studi Tematik dengan Pendekatan Kontekstual Abdullah Saeed) - Nur Wahid; Sul, Sulkifli; Makmur (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
The issue of abortion is an issue that raises controversy. Therefore, this study aims to reveal the insights of the Qur'an related to abortion. Based on this problem, the researchers tried to explore QS. al-An‘am verse 151 and QS. al-Isra' verse 31 by using Abdullah Saeed's contextual method. This research is qualitative research in the form of literature review. The results of this study indicate that (1) the act of abortion is something that is considered as an act of infanticide if done after the existence of life in the fetus, (2) abortion performed before the existence of life or after the existence of life in the fetus can be allowed as long as it meets the requirements set in the medical world.